Use of Infocus Media and Power Point Slides To Improve Learning Outcomes of Indonesian History Class X IPS 1 SMA Negeri 1 Sungai Lala Academic Year 2019/2020 - Meike Imbar; Rumiris Sihombing; Meity Najoan; Romi Mesra (Technium Social Sciences Journal, 2023)
The difficulty of teaching and learning in the topic of Indonesian history that frequently occurs in class X IPS 1 of SMA Negeri 1 Sungai Lala, namely the students’ lack of interest and attention to the presentation. Students prefer to redirect their attention to other activities, maybe as a result of boring teaching tactics that cause students to become bored. This study is a class action research (CAR) that was conducted in two cycles. Each cycle has four stages: preparation, activity, observation, and reflection. Colleagues made observations utilizing the observation sheet given. The findings revealed that students in the first cycle succeeded in improving their learning outcomes in Indonesian history, pupils that successfully finished the KKM grew to 23 pupils, or 71.88%, with an average learning accomplishment score of 74.84. The learning results of Indonesian History improved in cycle II, with all students, namely 32 students, attaining the KKM and being pronounced 100% complete with their studies, with an average score of 85.34. Based on these findings, it can be said that the use of Infocus media and power point slides may effectively and efficiently increase the learning outcomes of Indonesian History for class X IPS 1 SMA Negeri 1 Sungai Lala, which is carried out in two cycles.